PELATIHAN PENYUSUNAN PEMBUKUAN SEDERHANA UNTUK UMKM DI KABUPATEN SIDRAP - Rahman Pura; Sahidah Sahidah; Sufiati Sufiati; Eva Marin Sambo; Muhammad Faisal Arief; Ryan Putra Hafikar Suhardi (Nobel Community Services Journal, 2022)
The purpose of the activity is to increase the understanding of bookkeeping governance for Small and Medium Enterprises actors in Sidrap Regency. The method of delivering material in the form of lectures. The form of the lecture is used by the presenter to convey the activity material then followed by simulation and discussion. Training activities provide benefits in increasing the ability and ease of managing MSME finances